Reforming home care provision in Germany: evidence from a social experiment - Arntz, Melanie; Thomsen, Stephan L. (Discussion paper, 2008)
In a long-run social experiment, personal budgets have been tested as an alternative to the home care programs of the German long-term care insurance (LTCI). Due to extending the coverage beyond LTCI approved services and agencies, personal budgets may improve care outcomes compared to the provision of agency care at a constant benefit level, a highly desirable result in light of the ongoing demographic challenge. However, personal budgets also compete with the less generous cash option of the LTCI. Any transition from cash recipients to personal budgets increases LTCI spending, while care outcomes may remain unchanged if informal caregivers are crowded out by formal care. This paper compares care outcomes of the different home care programs and provides a rough cost analysis from the perspective of the LTCI. While personal budgets improve care outcomes compared to agency services, the nationwide introduction of personal budgets increases LTCI spending for former cash recipients without any traceable effect on their care outcomes.